A quarta revolução industrial - indústria 4.0: como os estudos acadêmicos estão tratando essa temática? - Guterres, Cláudio Victor Azevedo (Brasil, 2021)
The world is undergoing several changes and paradigms, the fourth industrial revolution or industry 4.0, is a revolution which will bring about changes in social, economic behavior and which will show new forms of market and industries with greater interaction than previously seen. These interactions come through functions of how this fourth industrial revolution is based on a system such as: Internet of Things, Big data, smart factories and Cyber security, cloud computing, 3D printing. This work seeks to present how the academy is presenting these concepts of this new revolution. In addition, this study will make it easier for readers to broaden their view to the importance in which we are experiencing.